IMPLEMENTASI SUPERVISI AKADEMIK DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PAI SD DI KECAMATAN LEKSONO KABUPATEN WONOSOBO TAHUN 2017 - rifqi muntaqo (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
Academic Supervision is a series of activities to assist teachers in developing their ability to manage the learning process to achieve learning objectives. Academic Supervision Implementation is needed to increase pedagogic competence of PAI SD teacher. The purpose of this research is to know how planning, implementation, evaluation, follow up and factors influencing academic supervision in improving pedagogic competence of teacher of PAI SD. The analysis used in this research is descriptive qualitative analysis. From the data analysis, it is known that academic supervision planning in improving pedagogic competence of PAI SD teachers in Leksono district of Wonosobo district is quite good, its implementation uses group and individual supervision technique and direct, indirect and collaborative approach implemented by principal and supervisor of PAI SD , evaluation and follow-up with assessment, analysis, guidance and suggestion, as well as the factors that influence them are the intensity of supervisor and principal in supervising PAI SD teacher in Leksono sub-district, Wonosobo district